'n Vergelyking van veerkragtige en nie-veerkragtige adolessente ten opsigte van beskermende faktore - Schlebusch, Bianca (University of the Free State, 2015)
South African middle-adolescents are confronted daily with developmental and environmental challenges as well as risk factors. Consequently, there is a need for the empowerment and development of resiliency amongst adolescents in South Africa in order to design more suitable interventions. Resilience is conceptualised from a normal developmental perspective as a sense of mastery and relatedness (both suggesting resilience) and emotional reactivity (suggesting vulnerability). The aggregation of these three components creates a resilience profile which reflects the adolescent’s unique strengths and weaknesses. A number of studies indicate that protective factors, both assets and resources, contribute to resilience. The aim of this study was to determine how male and female middle-adolescents with various resiliency profiles differ from one another with regard to protective factors. The different groups were compared in respect of five protective factors, namely intrapersonal, interpersonal and affective strengths, school functioning and family involvement. This study was quantitative and non-experimental and followed a criterion group design. The sample consisted of 973 Grade 10 learners, selected from each of the five districts in the Free State. The measuring instruments included a biographical questionnaire, Epstein and Sharma’s (1998) Behavioural and Emotional Rating Scale (BERS) and Prince-Embury’s (2007) Resiliency Scales for Children and Adolescents (RSCA). The results from the study indicate two important findings. First, it was found that both male and female participants scored low with regard to resilience and strengths. Secondly, a significant difference was found between the various groups with regard to the level of strengths that they use. It was shown, for instance, that groups that reported higher levels of resiliency tended to show lower levels of strengths. Consequently, the results are both surprising and worrying and lead to the following question: from which sources do adolescents draw in order to achieve resilience? The study revealed a clear need for more relevant research and measuring instruments in the South African context in order to effectively measure and comprehend these constructs.

Middel-adolessente in Suid-Afrika word daagliks met ontwikkelings- en omgewingsuitdagings sowel as risikofaktore gekonfronteer. Gevolglik is daar ’n duidelike oproep vir die bemagtiging en ontwikkeling van veerkragtigheid onder adolessente in Suid-Afrika, asook meer navorsing wat tot die ontwikkeling van toepaslike en nodige intervensies kan lei. Veerkragtigheid word vanuit ’n normale ontwikkelingsperspektief gekonseptualiseer as ’n sin van bemeestering en verwantskap (albei dui op veerkragtigheid), en emosionele reaktiwiteit (dui op kwesbaarheid). Die samevoeging van hierdie drie komponente skep ’n veerkragtigheidsprofiel wat die adolessent se unieke sterktes en kwesbaarheid weerspieël. ’n Aantal studies toon dat beskermende faktore, hulpbronne sowel as bates, tot veerkragtigheid bydra. Die doel van hierdie studie is om vas te stel hoe manlike en vroulike middel-adolessente met verskillende veerkragtigheidsprofiele van mekaar verskil ten opsigte van beskermende faktore. Die verskillende groepe is vergelyk ten opsigte van vyf beskermende faktore, naamlik interpersoonlike, intrapersoonlike en affektiewe sterktes, skoolfunksionering, en gesinsbetrokkenheid. Die studie is kwantitatief en nie-eksperimenteel van aard en volg ’n kriteriumgroepontwerp. Die steekproef bestaan uit 973 graad 10-leerders wat uit elk van die vyf distrikte in die Vrystaat gewerf is. Die volgende meetinstrumente is aangewend: ’n biografiese vraelys, Epstein en Sharma (1998) se Behavioural and Emotional Rating Scale (BERS) en Prince-Embury (2007) se Resiliency Scales for Children and Adolescents (RSCA). Die resultate lewer twee belangrike bevindinge. Eerstens is bevind dat die manlike sowel as vroulike deelnemers lae veerkragtigheid en sterktes toon. Tweedens is beduidende verskille geïdentifiseer tussen die verskeie groepe ten opsigte van die vlak van sterktes wat hulle gebruik. Dit het onder andere geblyk dat die groepe met hoër veerkragtigheid geneig is om laer vlakke van sterktes te toon. Hierdie bevinding is verrassend sowel as kommerwekkend en lei tot die volgende vraag: uit watter bronne put adolessente hulle veerkragtigheid? Die studie het ’n duidelike behoefte onthul aan meer relevante navorsing en toepaslike meetinstrumente in die Suid-Afrikaanse konteks om hierdie konstrukte effektief te meet en te verstaan.
Dissertation (M.A. (Counselling Psychology))--University of the Free State, 2015
Keywords: Resilience; Intrapersonal strengths; Interpersonal strengths; Affective strengths; School functioning; Family involvement; Assets; Resources; Gender; Middle adolescence; Normal development; Free State; South Africa